Youth Unemployment and Social Exclusion: Focus on the Nordic Countries - Paija, Rosa Maria (My University, 2021)
ABSTRACT The study’s goal is to examine, to what extent the youth unemployment of the Nordic countries is procyclical, as well as, to examine how different labour market policies could reduce the negative effects of unemployment. In addition, the study examines how unemployment effects the individual’s wellbeing, especial emphasis being on the effects on mental health. The study focuses especially on the effects on those young people of 15-29 years of age. Important terms that the study uses are NEET rate and Okun’s law. NEET rate tells, how large part of the total age group of people of 15-29 years of age in the country are those people who are not in education, employment, or training. Okun’s law explains how unemployment rate changes when GDP growth rate changes. The theory part of the thesis offers previous studies on the subjects of unemployment’s effect on wellbeing and explains the most important risk factors for unemployment, social exclusion, and poverty. In addition, the theory part compares the labour markets and labour market policies of the Nordic countries. The thesis has two research questions. The first research question examines how the NEET rates of Finland and Denmark change in regard to changes in GDP. The first model of the empirical part follows the framework of Okun’s law, and NEET rate replaces unemployment rate as the variable being explained. The second research question examines how economic cycles affect the sales of antidepressants in the Nordic countries. The research uses OLS regression analysis and the data for the variables is gathered from the databases of OECD and Nowbase. The study’s results are in line with previous studies. In the first model, it was observed that the NEET rates decrease when the GDP increases. The second model observed that the sales of antidepressants increase when the unemployment rate rises and the GDP decreases. The first model of the study used small datasets, which should be counted for when drawing conclusions from the results.

Tutkimuksen lähtökohtana on selvittää, missä määrin nuorisotyöttömyys Pohjoismaissa on riippuvainen taloussykleistä sekä miten erilaiset työvoimapoliittiset keinot pystyvät heikentämään työttömyyden negatiivisia vaikutuksia. Lisäksi tutkimuksen lähtökohtana on selvittää miten työttömyys vaikuttaa yksilön hyvinvointiin, ja erityisesti millainen vaikutus työttömyydellä on mielenterveyteen. Tutkimuksessa keskitytään erityisesti vaikutuksiin 15–29-vuotiailla nuorilla. Tärkeimpiä tutkimuksen käyttämiä käsitteitä ovat NEET-aste sekä Okunin laki. NEET-aste kertoo maassa olevien 15–29-vuotiaiden henkilöiden, jotka ovat koulutuksen, työn sekä harjoittelujen ulkopuolella, prosenttiosuuden koko ikäluokasta. Okunin laki selittää, miten työttömyysaste muuttuu, kun bruttokansantuotteen kasvuaste muuttuu. Teoriaosa selvittää aikaisempien tutkimusten valossa, miten työttömyys vaikuttaa hyvinvointiin sekä mitkä ovat keskeisimpiä riskitekijöitä työttömyydelle, syrjäytymiselle ja köyhyydelle. Lisäksi teoriaosa vertaa keskenään Pohjoismaiden työmarkkinoita ja työvoimapolitiikkaa. Tutkimusongelmia on tutkielmassa kaksi. Ensimmäinen näistä tutkii, miten Suomen sekä Tanskan NEET-asteet reagoivat bruttokansantuotteen muutoksiin. Tutkimuksen ensimmäinen osa seuraa Okunin mallin viitekehystä, ja NEET-aste korvaa työttömyysasteen paikan mallin selitettävänä muuttujana. Tutkimusongelmista toinen tutkii, miten taloussuhdanteet vaikuttavat masennuslääkkeiden myyntiin Pohjoismaissa. Tutkimuksessa on hyödynnetty pienimmän neliösumman menetelmää ja muuttujien data on kerätty Taloudellisen yhteistyön ja kehityksen järjestön tietokannasta sekä Nowbase-tietokannasta. Tutkimustulokset ovat linjassa aikaisempien aiheesta tehtyjen tutkimusten kanssa. Ensimmäisessä mallissa NEET-asteen havaittiin laskevan, kun bruttokansantuotteen kasvu kiihtyy. Vastaavasti tutkimuksen toinen malli havaitsi, että masennuslääkkeiden myynti kasvaa, kun työttömyysaste kasvaa ja vastaavasti, kun bruttokansantuotteen kasvuaste hiipuu. Tutkimuksen ensimmäinen malli käytti hyväkseen kooltaan pieniä aineistoja, mikä pitäisi huomioida tutkimustulosten hyödynnettävyydessä.
Keywords: unemployment; Nordic countries; social exclusion; Finland; labour market; unemployment rate; youth unemployment; education and training; young people; mental health; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|